2018
DOI: 10.1111/bjh.15702
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of dasatinib and exploratory genomic analysis in relapsed or refractory non‐Hodgkin lymphoma

Abstract: Summary Relapsed or refractory non‐Hodgkin lymphomas (NHLs) often carry poor prognosis and pose management challenges. We evaluated the safety and efficacy of dasatinib, a broad‐spectrum multi‐kinase inhibitor in relapsed/refractory NHL with correlative genomic analysis in a Phase I/II trial. The study included 33 patients with various sub‐types of NHL who had received at least one prior therapy. The most common sub‐types were diffuse large B‐cell lymphoma (24%), follicular lymphoma, grade 1/2 (21%) and periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…This patient's response suggests that G17V RHOA or VAV1 mutations do not necessarily predict dasatinib efficacy in AITL. Meanwhile, a phase I/II study of dasatinib as treatment for relapse/refractory non-Hodgkin lymphomas reported a patient with AITL achieving a PR, in agreement with our study (33).…”
Section: Discussionsupporting
confidence: 91%
“…This patient's response suggests that G17V RHOA or VAV1 mutations do not necessarily predict dasatinib efficacy in AITL. Meanwhile, a phase I/II study of dasatinib as treatment for relapse/refractory non-Hodgkin lymphomas reported a patient with AITL achieving a PR, in agreement with our study (33).…”
Section: Discussionsupporting
confidence: 91%
“…Dasatinib has been previously examined for its potential activity against non-Hodgkin lymphoma in a phase 1/2 clinical trial including 33 patients with heterogeneous B-and T-NHL histologies (30). Although it showed a limited number of both partial and complete responses with acceptable toxicities, this study included only 8 DLBCLs and did not explore the status of PI3K/AKT/ mTOR activation in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…We provide evidence that targeting LCK kinase activity with dasatinib has potent inhibitory effects on KHDRBS1-LCK-driven signaling, paving the way for therapeutic intervention in a clinical setting. Early-stage clinical trials suggest activity of dasatinib in PTCL-NOS 48 and TFH-related PTCL 49 . With the identi cation of the KHDRBS1-LCK gene fusion, we provide an additional biological basis to repurpose dasatinib for the treatment of PTCL-NOS.…”
Section: Discussionmentioning
confidence: 99%